Pathological fracture due to prolonged steroid use in a child with transverse myelitis - Ahmad Jabir Rahyussalim; Ronald Henry Tendean; Rizky Priambodo Wisnubaroto; Tri Kurniawati (Elsevier, 2019)
Introduction: Transverse myelitis (TM), a rare inflammatory disease of the spinal cord, is treated with corticosteroids that could result in other complications. Case report: We present the case of a 4-year-old boy with a closed left femoral fracture after he hit the floor. He was diagnosed with TM 1 year ago and was treated with oral methylprednisolone for 8 months. Discussion: In children, the prolonged use of corticosteroid enhances the osteoclast activity but reduces the osteoblast activity; this imbalance bone turnover causes osteoporosis that increases the fracture risk, which depends on the corticosteroid dose and treatment duration. Of note, the risk of fracture might last for years. Conclusion: The increased risk of fracture because of the prolonged use of corticosteroids might not impede the corticosteroid treatment if indicated. Hence, bone health status and nutritional monitoring must be performed at the beginning of treatment in children who need corticosteroid therapy with a cumulative dose >1 g/year. Keywords: Transverse myelitis, Corticosteroid, Fracture